2021
DOI: 10.1084/jem.20202187
|View full text |Cite|
|
Sign up to set email alerts
|

Mapping and role of T cell response in SARS-CoV-2–infected mice

Abstract: Virus-specific T cells play essential roles in protection against multiple virus infections, including SARS-CoV and MERS-CoV. While SARS-CoV-2–specific T cells have been identified in COVID-19 patients, their role in the protection of SARS-CoV-2–infected mice is not established. Here, using mice sensitized for infection with SARS-CoV-2 by transduction with an adenovirus expressing the human receptor (Ad5-hACE2), we identified SARS-CoV-2–specific T cell epitopes recognized by CD4+ and CD8+ T cells in BALB/c and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
158
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(167 citation statements)
references
References 42 publications
8
158
1
Order By: Relevance
“…Limited viral clearance in the respiratory tract was observed in CD8 + -depleted convalescent rhesus macaques upon SARS-CoV-2 rechallenge, implying that memory CD8 + T cells are required for the clearance of SARS-CoV-2 [ 18 ]. Furthermore, T-cell vaccination that does not elicit neutralizing antibodies partially protects SARS-CoV-2-infected mice from severe disease [ 19 ].…”
Section: An Overview Of Cd8 + T-cell Responses Against Sars-cov-2 In Patients With Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Limited viral clearance in the respiratory tract was observed in CD8 + -depleted convalescent rhesus macaques upon SARS-CoV-2 rechallenge, implying that memory CD8 + T cells are required for the clearance of SARS-CoV-2 [ 18 ]. Furthermore, T-cell vaccination that does not elicit neutralizing antibodies partially protects SARS-CoV-2-infected mice from severe disease [ 19 ].…”
Section: An Overview Of Cd8 + T-cell Responses Against Sars-cov-2 In Patients With Covid-19mentioning
confidence: 99%
“…It is now clear that SARS-CoV-2-specific CD8 + T-cell responses are detected in the acute and convalescent phases of COVID-19 [ 12 17 ]. In addition, recent studies using animal models have reported that CD8 + T cells contribute to protection from the development of severe COVID-19 [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a rhesus macaque model, CD8-depleted convalescent animals exhibited limited viral clearance upon SARS-CoV-2 re-challenge, suggesting that memory CD8 + T cells contribute to viral clearance during SARS-CoV-2 re-infection (McMahan et al, 2021). Furthermore, T-cell vaccination partially protected hosts from severe disease in a mouse model of SARS-CoV-2 infection (Zhuang et al, 2021).…”
Section: Memory T Cells After Recovery From Covid-19mentioning
confidence: 99%
“…No reuse allowed without permission. (27,28). We found that both groups developed similar levels of spike specific IgG (Fig 4D).…”
Section: Main Textmentioning
confidence: 56%